Implementation of Character Education in the Pancasila Student Profile Strengthening Project with the Local Wisdom Theme of Temu Manten in Class X at SMAN 3 Blitar - Hadi, Wenny Nova Octavia; Ayundasari, Lutfiah (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The research aims to discuss the implementation of character education through the Pancasila Student Profile Strengthening Project created by the Ministry of Education and Culture to overcome several problems in the world of education as an effort to build students' character in accordance with the values contained in Pancasila. In the world of education there are two problems, namely classical and modern problems. In this case, the researcher examines several phenomena of the implementation process, implementation implementation, and inhibiting and supporting factors in the field before and after the implementation of the P5 program by presenting data that is in accordance with the author's questions and assumptions, especially for class X students at SMAN 3 Blitar. In its implementation, schools are given full authority to implement these activities. Of the several themes contained in P5, the theme of local wisdom is very suitable to be applied at SMAN 3 Blitar because it has the potential to help introduce East Javanese local culture to the surrounding environment, build a sense of mutual cooperation, cooperation and achieve common goals. In this research, researchers used qualitative- descriptive methods. The results of this research show that the implementation of the Pancasila Student Profile Strengthening Project is quite good, but there are still several things that need to be improved, while the implementation itself is already strong in shaping the character of students in schools. So, if P5 activities are further optimized, the Pancasila character of students will be formed.